ANALISIS SEMIOTIKA PADA IKLAN POCARI SWEAT “SAAT SUHU TUBUH NAIK, JAGA CAIRAN TUBUH DENGAN POCARI SWEAT” - Tania, Sarah Dwi (LPPM Institut Teknologi Telkom Purwokerto, 2024)
Pocari Sweat is a drink product that replaces ION or body fluids. To promote its products, Pocari Sweat produces various advertisements that can add 9 products in a creative way. One of them is the Pocari Sweat advertisement entitled